Rethinking Design Thinking: Part I - Kimbell, Lucy (Design and culture, 2011)
The term design thinking has gained attention over the past decade in a wide range of contexts beyond the traditional preoccupations of designers. The main idea is that the ways professional designers problem-solve is of value to firms trying to innovate and to societies trying to make change happen. This paper reviews the origins of the term design thinking in research about designers and its adoption by management educators and consultancies within a dynamic, global mediatized economy. Three main accounts are identified: design thinking as a cognitive style, as a general theory of design, and as a resource for organizations. The paper argues there are several issues that undermine the claims made for design thinking. The first is how many of these accounts rely on a dualism between thinking and knowing, and acting in the world. Second, a generalized design thinking ignores the diversity of designers' practices and institutions which are historically situated. The third is how design thinking rests on theories of design that privilege the designer as the main agent in designing. Instead the paper proposes that attending to the situated, embodied routines of designers and others offers a useful way to rethink design thinking.